Experimental method research and miniature durability test-bench design of electric sliding door. (March 2023) - Lu, Wei; Yao, Zhipeng; Yao, Jia; Tang, Rongjiang; He, Shuilong
With recent enhancements in vehicle electrification, electric sliding doors have received significant research attention; however, the testing methods for the sliding doors components need to be improved. Herein, according to the durability evaluation index of sliding doors, a miniaturized durability test bench is designed for the electronic lock system and sliding door power output mechanism assembly. The motion trajectory of the electronic lock system can be fitted as a circular arc curve through dynamic characteristics analysis; therefore, a four-bar linkage with a flexible link is used to simulate the trajectory. Through the finite element simulation method, the test-bench stress is calculated at room temperature and a high temperature (75°C); this facilitates the selection of an appropriate material (GCr15). This experimental method is an economical, reliable, and accurate scheme to standardize the durability test of the electronic lock system and power output mechanism assembly.